The digital transformation of nursing practice: an analysis of advanced IoT technologies and smart nursing systems - Wang, Boyuan; Shi, Xiali; Han, Xihao; Xiao, Gexin (Frontiers in Medicine, 2024)
Facing unprecedented challenges due to global population aging 13 and the prevalence of chronic diseases, the healthcare sector is increasingly 14 relying on innovative solutions. Internet of Things (IoT) technology, by in-15 tegrating sensing, network communication, data processing, and security 16 technologies, offers promising approaches to address issues such as nurs-17 ing personnel shortages and rising healthcare costs. This paper reviews the 18 current state of IoT applications in healthcare, including key technologies, 19 frameworks for smart nursing platforms, and case studies. Findings indi-20 cate that IoT significantly enhances the efficiency and quality of care, par-21 ticularly in real-time health monitoring, disease management, and remote 22 patient supervision. However, challenges related to data quality, user ac-23 ceptance, and economic viability also arise. Future trends in IoT develop-24 ment will likely focus on increased intelligence, precision, and personali-25 zation, while international cooperation and policy support are critical for 26 the global adoption of IoT in healthcare. This review provides valuable in-27 sights for policymakers, researchers, and practitioners in healthcare and 28 suggests directions for future research and technological advancements.